Phenotypic and functional differences of HBV core-specific versus HBV polymerase-specific CD8+ T cells in chronically HBV-infected patients with low viral load - Schuch, Anita; Salimi Alizei, Elahe; Heim, Kathrin; Wieland, Dominik; Kiraithe, Michael Muthamia; Kemming, Janine; Llewellyn-Lacey, Sian; Sogukpinar, Özlem; Ni, Yi; Urban, Stephan; Zimmermann, Peter; Nassal, Michael; et al. (Gut, 2019)
Objective A hallmark of chronic HBV (cHBV) infection is the presence of impaired HBV-specific CD8+ T cell responses. Functional T cell exhaustion induced by persistent antigen stimulation is considered a major mechanism underlying this impairment. However, due to their low frequencies in chronic infection, it is currently unknown whether HBV-specific CD8+ T cells targeting different epitopes are similarly impaired and share molecular profiles indicative of T cell exhaustion. - Design By applying peptide-loaded MHC I tetramer-based enrichment, we could detect HBV-specific CD8+ T cells targeting epitopes in the HBV core and the polymerase proteins in the majority of 85 tested cHBV patients with low viral loads. Lower detection rates were obtained for envelope-specific CD8+ T cells. Subsequently, we performed phenotypic and functional in-depth analyses. - Results HBV-specific CD8+ T cells are not terminally exhausted but rather exhibit a memory-like phenotype in patients with low viral load possibly reflecting weak ongoing cognate antigen recognition. Moreover, HBV-specific CD8+ T cells targeting core versus polymerase epitopes significantly differed in frequency, phenotype and function. In particular, in comparison with core-specific CD8+ T cells, a higher frequency of polymerase-specific CD8+ T cells expressed CD38, KLRG1 and Eomes accompanied by low T-bet expression and downregulated CD127 indicative of a more severe T cell exhaustion. In addition, polymerase-specific CD8+ T cells exhibited a reduced expansion capacity that was linked to a dysbalanced TCF1/BCL2 expression. - Conclusions Overall, the molecular mechanisms underlying impaired T cell responses differ with respect to the targeted HBV antigens. These results have potential implications for immunotherapeutic approaches in HBV cure.
Published Online First 8 January 2019
Gesehen am 03.03.2020